OUTCOME OF VESICOVAGINAL FISTULA REPAIR AT TERTIERY HOSPITAL: COHORT STUDY - Liarto, Jason; Jufriady Ismy (Indonesian Journal of Urology, 2023)
Objective: This study aims to provide an evaluation of the outcome of patients with history of vesicovaginal fistula repair by assessing the success rate and complications that occur. Material & Methods: This study was a retrospective cohort study to describe the etiology, approach, and outcome in patients undergoing vesicovagina fistula repair. We analyzed the complication with vesicovaginal fistula type, etiology and technique used. Results: There were 10 vesicovaginal fistula patients, with mean age 33.4 ± 14.5 years. Both transabdominal and transvaginal approach were equally used. Sixty percent patient was successfully treated without complication. Forty percent patient with incontinence came with mild urinary incontinence and need further repair. Conclusion: Both transvaginal and transabdominal approach were equally effective to repair fistula with relatively low complication rate and high successful rate. Keywords: Vesicovaginal fistula, retrospective, transabdominal and transvaginal.